Radical and Atom Transfer Halogenation (RATH): A Facile Route for Chemical and Polymer Functionalization. Issue 10 (30th March 2016) - Han, Yi‐Jen; Lin, Chia‐Yu; Liang, Mong; Liu, Ying‐Ling
Abstract : This work demonstrates a new halogenation reaction through sequential radical and halogen transfer reactions, named as "radical and atom transfer halogenation" (RATH). Both benzoxazine compounds and poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) have been demonstrated as active species for RATH. Consequently, the halogenated compound becomes an active initiator of atom transfer radical polymerization. Combination of RATH and sequential ATRP provides an convenient and effective approach to prepare reactive and crosslinkable polymers. The RATH reaction opens a new window both to chemical synthesis and molecular design and preparation of polymeric materials. Abstract : A new radical and atom transfer halogenation (RATH) has been explored, showing great ability to generate the active sites of atom transfer radical polymerization and provide a versatile and convenient approach to design and synthesis of reactive/crosslinkable linear polymers and graft copolymers.